Including Students in Anti-Bias and Anti-Racism Work - Nicole M Thompson (Middle Grades Review, 2022)
This Practitioner Perspective describes how the anti-bias and anti-racism work began in our school district and specifically how it is going in the school where I work. I am part of the district’s Antibias Antiracist (ABAR) council and involved in bringing this information to the building’s staff, and I am also curious about investigating ways we can invite students into the conversation. Equity work takes time and not everyone feels equipped or able to have uncomfortable discussions with students. Regardless, we have a responsibility to do the work with our students every day. In her 2016 article “Don’t Say Nothing,” Jamila Pitts reminds educators that “we may be uncomfortable talking about race, but we can no longer afford to be silent” (Pitts, 2016). We are living in incredibly challenging times and now is certainly not the time to be reticent in teaching our students ways they can raise their voices.
Keywords: Anti-Bias; Anti-Racism; Middle School